2018
DOI: 10.2460/javma.253.4.470
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of risk factors for pasture-and endocrinopathy-associated laminitis in North American horses

Abstract: OBJECTIVE To investigate risk factors for the development of pasture- and endocrinopathy-associated laminitis (PEAL) in horses and ponies in North America. DESIGN Case-control study. ANIMALS 199 horses with incident cases of PEAL and 351 horses from 2 control populations (healthy horses [n = 198] and horses with lameness not caused by laminitis [153]) that were evaluated in North America between January 2012 and December 2015 by veterinarian members of the American Association of Equine Practitioners. PROCEDUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Prospective (longitudinal) cohort studies of laminitis are uncommon, but 2 recently completed prospective studies of disease incidence confirmed the importance of endocrinopathies and hyperinsulinemia in laminitis occurrence. It is important to note that the current study was not designed to evaluate the incidence of endocrinopathic laminitis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Prospective (longitudinal) cohort studies of laminitis are uncommon, but 2 recently completed prospective studies of disease incidence confirmed the importance of endocrinopathies and hyperinsulinemia in laminitis occurrence. It is important to note that the current study was not designed to evaluate the incidence of endocrinopathic laminitis.…”
Section: Discussionsupporting
confidence: 89%
“…A relationship between season and the incidence of laminitis has been described previously, with most studies indicating that spring and summer are associated with the greatest risk of disease . Also, the greatest proportion of cases in the current cohort of animals occurred in spring .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these endocrinopathies, EMS was the most prevalent underlying disease occurring in 82% of cases, whereas PPID was present in ~38% of the animals. Unsurprisingly then, both generalized and regionalized adiposity were evident in the cohort, with the findings of increased BCS and CNS consistent with the use of these phenotypic markers in the diagnosis of EMS, and with a recent study that found increased adiposity to be a risk factor for endocrinopathic laminitis . These data are important as recognition of an underlying endocrinopathy might enable the timely implementation of management (EMS) or treatment (PPID) strategies.…”
Section: Discussionsupporting
confidence: 78%
“…Endocrinopathic laminitis is associated with hyperinsulinemia and is a frequent sequelae to 2 common equine endocrinopathies: equine metabolic syndrome (EMS) and pituitary pars intermedia dysfunction (PPID) . Increased adiposity (generalized or regional, or both) is also a risk factor for the disease . Pasture‐associated cases of laminitis are associated with hyperinsulinemia (without any accompanying signs of inflammatory processes, such as diarrhea) and therefore are also likely to often fall under the umbrella of endocrinopathic laminitis …”
Section: Introductionmentioning
confidence: 99%